Performance of Coral Reef Management within Marine Protected Areas: Integrating Ecological, Socioeconomic, Technological, and Institutional Dimensions - Roni Bawole; Victor Rumere; Mudjirahayu; Thomas Frans Pattiasina (Institut Pertanian Bogor (IPB University), 2013)
This research studied the characteristics and approaches that contributed to the successful of coral reef management (CRM) efforts. One such characteristic occurred in most case studies was the importance of integrating ecological, socio-economic, technological use, and institutional dimensions during all processes. Based on a multi-dimensional analysis, the sustainability of CRM was 56.34% cumulatively, indicating a moderate level of management. This study further suggested the importance to improve technology and institution to achieve an effective CRM since both dimensions have contributed only 38.80% and 49.26% respectively. Stakeholder involvement was also central to the success of networking development within the management of Cenderawasih Bay National Park, specifically in facilitating the integration of ecological, socioeconomic, political will, and local cultural objectives in achieving an optimum planning objectives. Compilations of baselin information (both scientific and local knowledge) were important to evaluate the effectiveness of all processes and for adaptive management to increase its potential in the management strategies. Balancing the integration of all management dimensions (ecology, socio-economic, technology, and institution) in the whole processes with specific attributes in each case, would lead to an adaptive management for the implementation of conservation and management process.